Chronic Kidney Disease and Nutrition - Sofia Acevedo; Danielle Aycart; Jeanette Andrade (EDIS)
Chronic kidney disease (CKD) is considered a public health issue within the United States because an estimated 37 million adults or 15% of the population have this disease. CKD is a disease characterized by the gradual loss of kidney function. Early prevention techniques such as a well-balanced diet reduce the progression of this disease. The purpose of this new 6-page article is to provide an overview of CKD and nutritional considerations. Written by Sofia Acevedo, Danielle Aycart, and Jeanette Andrade, and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs429